Statins for aneurysmal subarachnoid haemorrhage: Another loss in translation - Matthew T. V. Chan (Journal of Neuroanaesthesiology and Critical Care, 2017)
Experimental evidence suggests that statin attenuates inflammation, oxidation, platelet aggregation and excitotoxicity. In brain ischemic models, statin administration produces vasodilatation and reduces neuronal apoptosis. It was hypothesized that statin administration may improve outcome by reducing delayed ischemic neurological deficit after aneurysmal subarachnoid haemorrhage. Earlier pilot trials suggested demonstrated encouraging results but the recent Simvastatin in Aneurysmal Subarachnoid Haemorrhage Trial, using simvastatin 40 mg per day, failed to demonstrate a benefit. Even at larger doses, simvastatin 80 mg per day did not reduce delayed ischemic neurological deficit. In common with many other interventions, statin represents another translational failure of presumed neuroprotective agents.